Faktor Yang Menyebabkan Terdakwa Melakukan Kekerasan Seksual - Budihastuti, Shinta Rukmi; Aryani, Esti (Wacana Hukum, 2022)
The creation of legal protection for children's rights is one of the main objectives to protect Indonesian children as fully as possible. The Pancasila and the 1945 Constitution of the Republic of Indonesia are the main guidelines as the legal basis for child protection so that all children's rights can be fulfilled and efforts to protect them can run in an orderly, orderly and responsible manner. It has been explained about the definition of a child based on Article 1 paragraph (1) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, which states that children are those who are not yet 18 (eighteen) years old, including children who still in the womb. The purpose of this study was to determine the factors that caused the defendant to commit sexual violence against the victim in the decision number 103/Pid.Sus/PN.Sgn. The type of research used in this research is normative legal research. The data analysis used in this research are: qualitative normative data analysis. Based on the results of the research that has been carried out, it is concluded that: The factors that caused the defendant to commit sexual violence against the victim in the decision Number 103/Pid.Sus/2019/PN.Sgn were changes in the cultural social system, which began to lead to advances in technology and information along with various impacts. The negative is very clear in this case. The defendant was introduced to the victim through social media such as Facebook. This type of social media is very vulnerable to being a place for child predators to find or get acquainted with potential prey. The defendant did the same to the victim in this case.